MODEL PEMBELAJARAN MASYARAKAT DALAM RANGKA SADAR PEDULI PAJAK (STUDI KASUS KPP PRATAMA BANDUNG CIBEUNYING) - M.E. Anni Yuliah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2012)
This study reviews the learning model towards conscious matter how tax can affect the increase in tax revenue optimization Primary tax service office Bandung Cibeunying. Community learning formulated on the formationmechanism of compliance is obtained from the analysis of the perception of the factors that influence the optimization ofÂ tax revenue. The method of research uses descriptive method in order to obtain a model of the learning society to formulate conscious care tax effect on tax revenue optimization. Descriptive method with a case study in Bandung Primary tax service office Cibeunying uses quantitative analysis with path analysis. The research finds that the tax administration does not directly influence tax compliance, tax authorities but through a process of productivity and taxation concepts that optimize tax revenue. Learning model society to realize tax matter affects the increase in tax revenue optimization in Bandung Primary tax service office Cibeunying. Implementation research seeks to contain the elements of a good educational decision-making, an enabling environment, and qualified human resources so that a positive image is obtained from 1) productivity resulting from empowerment, payroll proportionate and conducive working environment, 2) Administrai tax service that is able to generate customer satisfaction in order to reach customer loyalty, and 3) the concept of taxation that creates empowerment, independence and well-being.